Pemberdayaan Masyarakat Budikdamber sebagai Solusi Ekonomi Keluarga di Kampung Situpete, Tanah Sareal, Kota Bogor - Hamdani, Muchammad; Mujito, Mujito; Subagyo, Wawan Hari; Arafat, Yasir; Amelia, Imel (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Community service is a concrete form of the Tri Dharma of Higher Education, which emphasizes not only education and research but also direct contributions to society. Institut Teknologi dan Bisnis Dewantara (ITB) Cibinong conducted a community service program in Kampung Situpete, Sukadamai Village, Tanah Sareal District, Bogor City, with the theme of community empowerment through Fish Cultivation in Buckets (Budikdamber). This activity aimed to provide practical knowledge for utilizing limited space to raise fish and grow vegetables, thereby supporting household food security and creating opportunities for economic improvement. The methods applied included lectures, interactive discussions, and direct hands-on training, making it easier for participants to understand and apply the knowledge. The program received positive responses from the community, especially Karang Taruna Damai Mekar, and gained appreciation from local leaders.